Pengaruh penggunaan LKPD dalam model kooperatif tipe think talk write terhadap peningkatan keterampilan collaboration peserta didik - Weni Oktavia; Hidayati hidayati; Syafriani syafriani; Wahyuni satria dewi (PILLAR OF PHYSICS EDUCATION, 2020)
Student’s learning achievement in Physics especially aspects of skills are not optimal because they are less involved  in the learning process and they are less able to collaborate. Besides of that, teaching materials used in learning is still not diverse and not yet fully used . Therefore, researchers use the LKPD in the Cooperative Think Talk Write type as an alternative in improving student’s collaborative skill. This research is aimed to determine the effect of  using LKPD in the Cooperative Model Think Talk Write Type Against the Improving of Collaboration Skills in 10th Grade Students of SMAN 1 Pariaman. This research is using a quasi-experimental design with a randomized control group only design. The populations were students in X MIPA 1 - X MIPA 5 that were taught by the same teacher with the same teaching hours at SMAN 1 Pariaman and registered in 2019/2020. Researcher used purposive sampling technique. Collaboration skills were used as a data research. Instrument of this research a performance assessment sheet. The data were analyzed by two average similarity tests. The results showed the average value of Physics learning for the collaboration skills competence in the experimental class is 80.06 and  the control class is 68.90. The conclusion of the research is there is a significant influence from the use of LKPD in the Cooperative Model Think Talk Write Type towards the Improvement of Collaboration Skills in 10th Grade Students of SMAN 1 Pariaman